Saving images. Memory and oblivion of knowledge in the digital age (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
Some of the contemporary phenomena that concern memory and the transmission of knowledge such as the digitization of archives, the rapid obsolescence of digital technologies, the power of data cloud service providers who store information, question the ways of knowledge transmission that have consolidated over the millennia. We live in an age of excess of images, but most of them could be forgotten. From the images carved, engraved and drawn on stone to those downloaded onto digital mobile devices – through papyri, tapestries, canvases, paper... – there has been a process of accelerating of the consumption of images, of democratising of their production tools and at the same time of dematerialising them. Can the dematerialization and digitalization of information be the solution to the immanent question of memory of contemporaneity? Or will it be the cause of the oblivion of our culture? Which and how many of these have arrived to us and which and how many have been lost due to technical and technological causes? How many of the images of contemporaneity will survive our age? Will we be able to transfer to future generations the immense amount of information and images that we produce every day? In this article we want to discuss these questions by investigating the role of images in the transmission of culture, with reference to contemporary phenomena and different case studies from different cultures and eras, to conclude by discussing the risks associated with the digitization of knowledge and images as a privileged means of transmission of knowledge and cultures.